Caspase-mediated pathways in retinal ganglion cell injury: a novel therapeutic target for glaucoma - Rajakrishna, Nisha; Lim, Seok Ting; Wang, Xiaomeng; Wong, Tina T. (Frontiers in Cell and Developmental Biology, 2025)
Glaucoma is a complex disease of the optic nerve leading to vision loss and blindness, with high worldwide incidence and disproportionate prevalence in older populations. Primary open-angle glaucoma, caused by a reduction in outflow of aqueous humor through the trabecular meshwork, is the most common subset of the disease, though its underlying molecular mechanisms are not well understood. While increased intraocular pressure is the most common risk factor in glaucoma progression, the disease is ultimately characterized by the loss of retinal ganglion cells (RGCs) and destruction of the optic nerve. Given the irreversibility of RGC death, neuroprotection of RGCs is a promising avenue of glaucoma prevention and treatment. The caspase family of proteins are integral members of the apoptotic death cascade. They have been shown to play a significant role in RGC death in numerous models of retinal injury. Direct inhibition of several caspase family members, through targeted siRNAs and peptidomimetics, demonstrate promising capacity to reduce caspase expression and preserve RGCs following intraocular pressure increase or optic injury. A wide variety of alternative therapeutics targeted for RGC survival, including neurotrophins, immunomodulators, cytoprotectants, and endogenous hormones, also display indirect caspase-inhibiting capabilities. Following intraocular pressure increase or external retinal injury, both direct and indirect caspase inhibitors elicit higher RGC counts, increased RGC layer thickness, and attenuation of RGC damage, clearly demonstrating the neuroprotective abilities of caspase inhibitors. Caspase inhibition, particularly by direct approaches of siRNA or peptidomimetic-based therapeutics, has the potential to achieve substantial neuroprotection in the glaucomatous eye.